Best of the Philippines. (Almandine, Garnet & Sorrel, 1989)
A full-color, illustrative publication that lists different important personalities in different fields and their outstanding contributions to a given profession: visual arts, fashion design, performing arts, movies, interior design, shopping, jewelery, collections, sports, photography, as well as different exotic destinations in the Philippines and leading hotels and restaurants.